Learning and school performance: effects of inclusive education in pandemic times (Research, Society and Development, 2022)
The covid-19 pandemic resulted in several changes involving human activities, including the routine of thousands of students both in regular education and in the perspective of inclusive education. This work aimed to reflect on the consequences of inclusive education in times of a pandemic, as well as to analyze inclusive education and identify the implications of the pandemic context for all agents involved. The question that guided this study was to understand the dichotomy: Learning and School Performance: Effects of Inclusive Education in times of Pandemic. Thus, the bibliographic research method, of qualitative and quantitative character, was used. As data collection, Google Scholar and Scielo platforms and documents were used to deepen the theme proposed in the research. Finally, it must be considered that the pandemic has brought urgent and significant changes through the use of digital technologies, in the conduct of inclusive education and that it is necessary to have public educational policies that consider the different contexts, with or without crisis, so that minimizes the increase of those excluded by the current context.